NUMERICAL MODEL FOR OPTIMIZING GABIONSâ CONFIGURATION TO MINIMIZE WAVE RUN-UP - Dewata, Dara
Human activities and population growth in coastal areas, as well as the natural phenomenon of the waves themselves, can cause several coastal problems. Furthermore, the fact that Indonesia is one of the world's most vulnerable countries to sea-level rise, as well as the fourth most populous country, increases the risk of coastal hazards in our country every year. Consequently, it is critical to have an optimal approach in designing a sea defense structure in order to reduce the risk of coastal hazards. One of the factors to consider when constructing a sea defense structure is the potential risk of wave run-up. Therefore, in this research, we investigated the wave run-up phenomenon to develop an optimization model capable of identifying the optimum configuration of our proposed sea defense structure, the gabions wall. The wave run-up is modeled using the Non-Linear Shallow Water Equations (NSWE) and the mathematical model is then solved numerically using the finite volume method on a staggered grid with a wet-dry procedure which has an important role to obtain accurate wave run-up. Several benchmark tests were done to establish the robustness of the model and it shows a good agreement between the numerical result and the analytical solutions as well as the experimental data. Moreover, our findings show that the gabions wall can significantly reduce the wave run-up height, but the combination of width and height of each gabions’ step results in a random pattern of wave run-up height. To solve that problem, we defined the optimization problem and used the genetic algorithm (GA) method to solve it. Following that, our optimization model can find the optimum gabion's configuration that produces the smallest possible wave run-up height and satisfy the optimization constraints. Once we have determined the optimum configuration of the gabions wall, it will be useful in the decision-making process when constructing a coastal protection structure.